Green Intellectual Capital and Financial Performance: The Role of Sustainable Growth Rate - Hulaemah, Eem Hulaemah; Windu Mulyasari (Accounting and Sustainability, 2024)
This study aims to analyze the effect of Green Intellectual Capital on financial performance with Sustainable Growth Rate as an intervening in variable energy sector companies listed on the Exchange for the Indonesia Stock period 2021-2023. Using a quantitative approach, this study applies a panel data and the Sobel test regression model to test the causal relationship between variables. The results showed that Green Structural Capital has a has a positive and significant effect on financial performance, while Green Human Capital negative effect on financial performance. Green Relational Capital does not show a significant effect. Sustainable Growth Rate proved to have a positive influence on financial performance, but did not mediate the relationship between Green Intellectual Capital and financial performance. These findings indicate that although the concept of Green Intellectual Capital is an important strategy in the context of sustainability, its implementation does not always have a direct impact on financial performance. Therefore, a more comprehensive strategy is needed to optimize the role of Green Intellectual Capital in supporting sustainable growth.